Effect of dexmedetomidine infusion on N-terminal pro-B-type natriuretic peptide level in patients with femoral shaft fractures under general anesthesia (Bangladesh Journal of Pharmacology, 2016)
This study was performed to assess the effect of dexmedetomidine on the level of N-terminal proB-type natriuretic peptide (NT-pro-BNP) in patients undergoing major orthopedic surgery. Patients undergoing general anesthesia for femoral shaft fracture surgery were randomly assigned to either 0.5 µg/kg/hour dexmedetomidine or normal saline. Changes in levels of NT-pro-BNP and hemodynamic parameters were compared. Data of 46 patients were analyzed and it was found that the change in NT-pro-BNP levels in the dexmedetomidine group was significantly less than the control group (p = 0.001). In addition, bleeding, changes in systolic and diastolic blood pressure in dexmedetomidine group was significantly less than the control group (p?0.001). It is likely that dexmedetomidine infusion can reduce the rise of NTpro-BNP level and therefore is associated with better cardiac outcome. In addition, dexmedetomidine infusion can achieve hemodynamic stability in femoral shaft fracture under general anesthesia.